Adoption of Robotic Process Automation (RPA) to Streamline Back-Office Operations and Improve Cost Efficiency in Medium Enterprises - Zeze Zakaria Hamzah; Aria Elshifa; Zhala Rahman Aliyeva (Management Dynamics: International Journal of Management and Digital Sciences, 2024)
The adoption of Robotic Process Automation (RPA) has emerged as a crucial strategy for medium-sized enterprises (SMEs) to streamline back-office operations, enhance productivity, and reduce operational costs. RPA involves the use of software robots to automate repetitive, rule-based administrative tasks, allowing employees to focus on more complex, value-added activities. This study explores the implementation of RPA in medium enterprises, focusing on its impact on cost efficiency, administrative workload reduction, and operational performance. The research uses a case study approach, analyzing medium enterprises that have adopted RPA to assess the effectiveness of automation in improving business processes. Data collection methods include interviews, surveys, and company reports to evaluate how RPA affects workload, accuracy, and cost savings. The findings indicate that RPA significantly reduces manual administrative tasks, leading to faster processing times, lower error rates, and substantial cost savings. Employees in enterprises that adopted RPA reported increased job satisfaction due to the reduction of monotonous tasks and the opportunity to engage in more strategic work. However, challenges such as employee resistance, data security concerns, and system integration complexities were also identified. The study compares RPA’s impact with traditional manual processes, highlighting improvements in speed, accuracy, and overall cost efficiency. Additionally, the study compares RPA adoption across industries such as manufacturing, retail, and service, revealing sector-specific challenges and successes. The paper concludes by emphasizing the practical implications for SMEs, suggesting that RPA can optimize business operations and urging further research on its long-term effects on employee roles and organizational culture.